(untitled) (Baghdad Science Journal, 2025)
This research studied the effect of magnetized water in concrete preparation and its effect on the presenting of cement in concrete mixtures also to find the ability of reducing the amount of cement in preparing one cubic meter, this is not exceed than 10% in one mixture , The experiments showed the preparation of standard cubes from the concrete which was used two kind of water magnetized water which was prepared by passing the tap water through the systems of different magnetic strength in terms of (6000,9000) Gauss and the ordinary water . The velocity of water through the magnetic field, which gives us the highest value for the compressive strength, was up to 1m/sec. to determine the best magnetic intensity, we examined The compressive strength and workability of the concrete which is not effect on the efficiency of the structure because of reducing cement percentage. The tests for compressive strength on concrete mixture with magnetized water appeared an increase (24%) compared to the results of the control cubes with fixed amount of cement; also the cubes with less amount of cement showed an increase (22%) and both cases give us higher compressive strength and workability.